Basic equality - Sagar, Paul (Princeton Princeton University Press, 2024)
What makes human beings one another$1 (Bs equals? That we are (3z(Bbasic equals(3y (Bhas become a bedrock assumption in Western moral and political philosophy. And yet establishing why we ought to believe this claim has proved fiendishly difficult, floundering in the face of the many inequalities that characterise the human condition. In this provocative work, Paul Sagar offers a novel approach to explaining and justifying basic equality. Rather than attempting to find an independent foundation for basic equality, he argues, we should instead come to see our commitment to this idea as the result of the practice of treating others as equals.s